Democracy in Flux: Political Alliances and the Role of Religion in Indonesia and Turkey - Syam, Mutmainna (Muslim Politics Review, 2024)
Home to approximately one-fifth of the global Muslim population, Indonesia and Turkey underwent democratization efforts in the early 2000s. However, two decades later, both countries are facing growing tendencies of neo-autocratization. Both countries also face challenges typical of liberal democracies, such as the rise of populist leaders, concentration of power, elite-driven politics, resource exploitation, and growing inequality. This paper analyzes how political alliances influence the reconfiguration of political parties in the two countries. Contributing to the literature on change and adaptation in democracies, as well as addressing the scarcity of comparative studies between Indonesia and Turkey, this paper poses the following questions: How are political alliances formed and structured in Indonesia and Turkey? What role does religion play in shaping these alliances? What are the implications of political alliances on democracy in both countries? In this paper, I show how, during political rivalry—especially in electoral competition—political alliances in Indonesia are formed suddenly within a messy landscape, while in Turkey, it is a gradual and slow process in which rigid ideological boundaries lead to alliances across ideologies. Both conditions contribute to autocratization tendencies, creating no real opposition in Indonesia and a relatively weak opposition in Turkey. In this process, religion is central in both countries and is intertwined with nationalism in different ways.